Effects of Water Regimes on Methane Emissions in Peatland and Gley Marsh - Zhu, X. (2020)
The highest emission pulses were observed between 4 and 9 d after the water table increased according to the models. Peak pulse emissions significantly increased by 41% in peatland and 109% in gley marsh after rewetting compared with that in the steady 0‐cm water table treatment. Peatland soils had higher CH4 emissions than gley marsh soils under steady water table treatments (P < 0.01). This study shows that large pulses of CH4 can be emitted during short‐duration drying–wetting episodes. If these pulses are not accounted for in budgets, CH4 emissions may be incorrectly assessed when comparing with field measurements during regularly spaced sampling intervals over only a few days or weeks by the static opaque chamber technique. Accurate estimates of CH4 budgets not only depend on increased measurement frequency but by necessity should incorporate weather events that cause rapid changes in the soil moisture regime.